An econometric analysis of the interrelations between shadow and official economy on economic growth - Adrián Ríos Blanco (Revista Galega de Economía, 2022)
Using panel data from 29 OECD countries between 1991-2015 in an economic growth model of two sectors with heterogeneous productivities, we show that the underground economy exerts an effect on the official one. Both economies move in opposite directions because when hidden GDP grows, economic growth is damaged through a negative externality or spillover. However, the marginal productivity of the shadow economy is found to be lower than that of the official one, so, it is possible to some extent that the rules available to control it are effective. The application of different econometric techniques leads to similar conclusions demonstrating the robustness of the results.